Exploring the Extremes: Characterizing a New Population of Old and Cold Brown Dwarfs - Aaron M. Meisner; S. K. Leggett; Sarah E. Logsdon; Adam C. Schneider; Pascal Tremblin; Mark Phillips (The Astronomical Journal, 2023)
Mapping out the populations of thick disk and halo brown dwarfs is important for understanding the metallicity dependence of low-temperature atmospheres and the substellar mass function. Recently, a new population of cold and metal-poor brown dwarfs has been discovered, with T _eff ≲ 1400 K and metallicity ≲−1 dex. This population includes what may be the first known “extreme T-type subdwarfs” and possibly the first Y-type subdwarf, WISEA J153429.75−104303.3. We have conducted a Gemini YJHK / Ks photometric follow-up campaign targeting potentially metal-poor T and Y dwarfs, utilizing the GNIRS and Flamingos-2 instruments. We present 14 near-infrared photometric detections of eight unique targets: six T subdwarf candidates, one moderately metal-poor Y dwarf candidate, and one Y subdwarf candidate. We have obtained the first-ever ground-based detection of the highly anomalous object WISEA J153429.75−104303.3. The F110W − J color of WISEA J153429.75−104303.3 is significantly bluer than that of other late T and Y dwarfs, indicating that WISEA J153429.75−104303.3 has an unusual spectrum in the 0.9–1.4 μ m wavelength range which encompasses the J -band peak. Our J -band detection of WISEA J153429.75−104303.3 and corresponding model comparisons suggest a subsolar metallicity and temperature of 400–550 K for this object. JWST spectroscopic follow-up at near-infrared and mid-infrared wavelengths would allow us to better understand the spectral peculiarities of WISEA J153429.75−104303.3, assess its physical properties, and conclusively determine whether or not it is the first Y-type subdwarf.